The fluoride content of drinking water and caries experience in 15 – 19 year old school children in Ibadan, Nigeria (2008)
Fluoride, a trace element with anticariogenic benefit may either occur naturally or be added to drinking water sources. This study aimed at determining the fluoride level of the different drinking water sources in Ibadan, Oyo State, Nigeria and to relate this with the caries experience of secondary school children in the city. Sixteen samples of the drinking water sources from various locations in the five local government areas of the city were analysed for fluoride concentration. The locations were selected around the vicinities of the secondary schools used for caries study. Nine hundred and fifty five students aged 15-19 years randomly selected from eleven secondary schools in Ibadan metropolis were examined for dental caries over a period of 4-5 months. Only teeth with obvious cavitations were recorded as being carious using the WHO standard method. Teeth grossly covered with calculus and third molars were excluded. No radiograph was taken. The fluoride level of the different water sources was between 0.02 and 0.03ppm. Forty-four (4.6%) of the children had dental caries. There was no statistically significant difference between either DMFT and gender (t = 0.67, p = 0.91) or DMFT and age (F=1.488, p=0.224). However, females had a slightly higher mean DMFT than males and the highest mean DMFT (2.67 + 1.15) was found among the 19- year- old children. Twenty-three (52.3%) of the students with caries had only one carious tooth while only two had four carious teeth each. In conclusion, both the fluoride level and caries prevalence were low.